Spider silk as an active scaffold in the assembly of gold nanoparticles and application of the gold-silk bioconjugate in vapor sensing - Singh, Amit; Hede, Shantesh; Sastry, Murali (Small, 2007)
Spider silk is being viewed with interest by materials scientists due to its excellent resilience and mechanical properties. In this paper we show that spider silk is an excellent scaffold for the one-step synthesis and assembly of gold nanoparticles. Formation of a gold nanoparticle-spider-silk bioconjugate material is accomplished by simple reaction of the fibers with aqueous chloroauric acid. The gold nanoparticles thus formed are strongly bound to the spider-silk fiber surface enabling study of the electrical properties of the nano bioconjugate. Using the well-known contraction/expansion behavior of the fibers in solvents of varying polarity, we show that exposure of the gold nanoparticle-spider silk bioconjugate to vapors of methanol and chloroform leads to changes in electrical transport through the nanoparticles and thus, the possibility of developing a vapor sensor. The bioconjugate shows excellent response time and cycling efficiency to methanol vapors. The activation energy of electron transport from one gold nanoparticle to another in the nanobiocojugate was determined from temperature-dependent electron-transport measurements to be approximately 1.7 eV.
Keywords: bioconjugates; Gold; Nanoparticles; sensors; spider silk

Shape and size selective separation of gold nanoclusters by competitive complexation with octadecylamine monolayers at the air-water interface - Pasricha, Renu; Singh, Amit; Sastry, Murali (Journal of Colloid and Interface Science, 2009)
The paper presents a time-dependent study of shape-dependent preferential complexation of gold nanoparticles to the octadecyl amine (ODA) monolayers at the air-water interface. Room temperature reduction of chloroaurate ions using lemon grass leaf extract yields a Mixture of spherical and triangular nanoparticles, which were used for this study. These nanoparticles have a net negative charge on their surface due to the presence of biomolecules from plant extract and thus a strong attractive electrostatic interaction with the positively charged ODA monolayers drives the complexation process. The extent of preferential complexation of the gold nanoparticles to the ODA monolayers is a function of the charge on the particles and the relative mobility of the nanoclusters in the medium. The complexation process has been followed in real time by a host of techniques such as surface pressure-area (pi-A) isotherms, UV-vis-NIR spectroscopy and Brewster angle microscopy. The charge and mobility of the gold nanoparticles was confirmed by measurement of their electrophoretic mobility. Langmuir-Blodgett films of the nanogold-ODA composites have been characterized by UV-vis-NIR spectroscopy, Fourier transform infrared spectroscopy, and transmission electron microscopy. These measurements clearly indicate that the cluster mobility and complexation increase with decreasing cluster size. In the competitive complexation process of large and small gold particles, it was observed that some bigger gold particles were also incorporated into the amine matrix even though the cluster mobility is higher for smaller gold particles. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: Competitive complexation; gold nanoparticles; Langmuir-Blodgett technique; ODA monolayer